Yield Enhancement of T. Aman Rice in Salinity Affected Area of Noakhali District of Bangladesh Through Adoption of Variety and Gypsum Fertilizer Application - Kabir, Md Humayun; Islam, Md Ariful; Jahan, Nilufar Akhtar; Habiba, Ummay; Kader, Md Abdul; Hasan, Ahmed Khairul (Research in Agriculture Livestock and Fisheries, 2020)
An experiment was conducted in the farmer’s field at the Moddho Jutkhali village, Subornochar, Noakhali, a salinity affected area of Bangladesh to investigate the effect of variety and gypsum fertilizer on the yield of transplant aman rice under salinity condition during July to December, 2017. The experiment was laid out in a two factor split-plot design with three replications consisting of three aman rice varieties viz., Swarna (V1, an indian variety adapted to that locality), BRRI dhan52 (V2) and Binadhan-7 (V3) and three levels of gypsum fertilizer viz., 0, 75 and 150 kg gypsum ha-1. Yield components and yield of transplant aman rice were significantly influenced by variety, level of gypsum and their interactions. Among the varieties, Swarna produced the tallest plant height (126.7 cm), highest number of grains panicle-1 (76.30), weight of 1000 grains (25.80 g), grain yield (5.44 t ha-1), straw yield (7.07 t ha-1), and biological yield (12.51 t ha-1) while Binadhan-7 showed lowest values of these respective parameters but number of total tillers hill-1 (9.99) and number of effective tillers hill-1 (8.94) were maximum in Binadhan-7. Among three gypsum levels, most of the yield contributing characters showed highest values for 150 kg gypsum ha-1 that’s why grain yield was also highest (5.32 t ha-1) for this treatment. On the other hand lowest grain yield (4.92 t ha-1) was found when no gypsum was applied. In case of treatment interaction, highest number of grains panicle-1 (80.23) and highest grain yield (5.69 t ha-1) were produced when Swarna was cultivated with 75 kg gypsum ha-1 while lowest values of grain, straw and biological yields (4.36, 5.11 and 9.47 t ha-1, respectively) were found when Binadhan-7 was cultivated without applying any gypsum. Therefore, it can be concluded that the variety Swarna with 75 kg gypsum ha-1 can be practiced for the cultivation of transplant aman rice in the salinity affected area of Noakhali, Bangladesh to obtain the highest grain yield. Res. Agric., Livest. Fish.7(3): 363-371, December 2020